2023
DOI: 10.3389/fpubh.2023.1216704
|View full text |Cite
|
Sign up to set email alerts
|

Stability and genetic insights of the co-existence of blaCTX-M-65, blaOXA-1, and mcr-1.1 harboring conjugative IncI2 plasmid isolated from a clinical extensively-drug resistant Escherichia coli ST744 in Shanghai

Jun Feng,
Huanyu Wu,
Yuan Zhuang
et al.

Abstract: BackgroundCo-existence of colistin, β-lactam and carbapenem in multidrug-resistant Enterobacteriaceae isolates poses a serious threat to public health. In this study, we investigated and characterized the co-occurrence of blaCTX-M-65, blaOXA-1, and mcr-1.1 strain isolated from a clinical extensively-drug-resistant Escherichia coli ST744 in Shanghai.MethodsAntimicrobial susceptibility test was carried out by agar dilution methods. Whole genome sequencing was conducted, and resistance genes, and sequence types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…IncI2 plasmids have been identified in several mcr-1 cases on various hosts worldwide [ 32 ], while the IncX4 plasmid type has been recognized as the primary carrier of the mcr-1 gene in isolates from healthy individuals in China [ 33 ], as well as in Enterobacteriaceae isolates carrying carbapenem and mcr-1 resistance genes simultaneously from clinical patients in Thailand [ 34 ]. Our study identified the presence of mcr-1 genes on both IncI2 and IncX4 plasmids, which have been recently observed in E. coli isolates from food, livestock, and humans across various countries [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 66%
“…IncI2 plasmids have been identified in several mcr-1 cases on various hosts worldwide [ 32 ], while the IncX4 plasmid type has been recognized as the primary carrier of the mcr-1 gene in isolates from healthy individuals in China [ 33 ], as well as in Enterobacteriaceae isolates carrying carbapenem and mcr-1 resistance genes simultaneously from clinical patients in Thailand [ 34 ]. Our study identified the presence of mcr-1 genes on both IncI2 and IncX4 plasmids, which have been recently observed in E. coli isolates from food, livestock, and humans across various countries [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 66%
“…Our study suggests a lower prevalence (0.33%, 1/306) of mcr-1 in LTCF wastewater than that reported from other LTCFs in other countries such as Italy ( 31 ) and the Netherlands ( 18 ). Furthermore, the prevalence was also lower than E. coli strains isolated from human populations in Shanghai ( 25 , 32 , 33 ), and it was not as high as that found in E. coli isolated from hospitalized companion animals ( 34 ). Given that those E. coli strain carriers were only detected during the prevalence survey, most carriers remain undetected in Shanghai.…”
Section: Discussionmentioning
confidence: 71%